Design and develop robotic arm for automated guided conveyor - Gapar, Francis Giang (2011)
This thesis is related to the mechanism of a robotic arm that serves as a tool to lift an object from one place to another where it is widely used in the factory. The study of this material was analyzed using computer software that can calculate the finite element of linear stress analysis of each mechanical components of robotic arm. Results of this analysis will be a reference to select suitable material. In this project, the aluminium 6061 was used. In addition, the selection of electrical components used in the robotic arm is also taken into account by calculating the inverse kinematic and forward kinematic of this robotic arm movement. Besides that, the forces exerted on the robotic arm are also calculated to ensure the mechanical components of the robotic arm is not easily broken or damaged. Referring to the result obtained, a robotic arm resistance depends on the motor used. Therefore, the compatibility of motor torque with the robotic arm design is made is important because it affects the stability of the robotic arm.